2009
DOI: 10.1071/ah090434
|View full text |Cite
|
Sign up to set email alerts
|

Standardising practices through form design and education improves insulin management

Abstract: Diabetes is common in hospitalised patients and insulin is frequently required for management. Insulin is a high-risk drug, accounting for about 15% of reported medication-related incidents. Despite its complexity, insulin management in hospitals is often undertaken by junior and nonspecialist staff. Improving insulin management requires addressing safe prescribing and administration as well as quality use of insulin. Common errors in insulin use are well documented and can be addressed through form design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The introduction of simple, small focused interventions led to an improvement in the completeness and accuracy of insulin prescribing, particularly when they involved ‘hard stops’ (such as pre‐printing ‘units’ on dedicated insulin prescription charts to avoid misinterpretation of ‘u’) . McIver et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of simple, small focused interventions led to an improvement in the completeness and accuracy of insulin prescribing, particularly when they involved ‘hard stops’ (such as pre‐printing ‘units’ on dedicated insulin prescription charts to avoid misinterpretation of ‘u’) . McIver et al .…”
Section: Resultsmentioning
confidence: 99%
“…McIver et al . implemented a standardized insulin prescribing form incorporating pre‐printed ‘units’ and mealtime associations . As a result, they reported a reduction in the opportunity for error as a result of non‐standard abbreviations from 41.8% to 12.2% and as a result of unclear frequency from 65.9% to 6.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies had assessed the effectiveness of an insulin‐prescribing chart. In Queensland, an intravenous as well as subcutaneous insulin chart had been developed, and although glycaemic control was not significantly different following the introduction of the subcutaneous insulin chart, there was improvement in the clarity of insulin prescription and the frequency of usage of supplemental insulin . Cheung et al performed an audit on their locally developed subcutaneous insulin chart, which was similar to the NSW ASCIPC .…”
Section: Discussionmentioning
confidence: 99%
“…In Queensland, an intravenous as well as subcutaneous insulin chart had been developed, and although glycaemic control was not significantly different following the introduction of the subcutaneous insulin chart, there was improvement in the clarity of insulin prescription and the frequency of usage of supplemental insulin. 10 Cheung et al performed an audit on their locally developed subcutaneous insulin chart, which was similar to the NSW ASCIPC. 11 Following the introduction of their insulin chart, Cheung et al reported an increase in the number of BGL performed daily and a higher proportion of BGL between 4.0 and 9.9 mmol/L (54.1 vs 51.8%, P = 0.01).…”
Section: Discussionmentioning
confidence: 99%